2023
DOI: 10.1088/1755-1315/1144/1/012013
|View full text |Cite
|
Sign up to set email alerts
|

Empowering women for disaster risk reduction: a case study of geologically based disaster at Yan, Kedah, Malaysia

Abstract: The effects of disaster impact all levels of society equally. However, both men and women response to disaster differently. It is critical to acknowledge that both genders have different roles, responsibilities, access, and control over resources as well as how they are affected by crisis and disaster. This paper seeks to build an initial understanding on the importance of gender perspective through review of literature and single case study of Community Based Disaster Risk Management (CBDRM) program conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Environment Women answer the need for empirical insightsvital information, skills, resources, and experiences for building resilience strategies in disaster risk reduction, which allows for adaptive capacity for women and men (Evertsen, 2023;Tobi et al, 2023). Addressing creatively the barriers, including subpar working conditions for women and institutional failure or poverty, which restrict women's agency and hinder their ability to adapt effectively, could potentially enhance their resilience and adaptability (Rao et al, 2019).…”
Section: Research Implication For Policymakersmentioning
confidence: 99%
See 1 more Smart Citation
“…Environment Women answer the need for empirical insightsvital information, skills, resources, and experiences for building resilience strategies in disaster risk reduction, which allows for adaptive capacity for women and men (Evertsen, 2023;Tobi et al, 2023). Addressing creatively the barriers, including subpar working conditions for women and institutional failure or poverty, which restrict women's agency and hinder their ability to adapt effectively, could potentially enhance their resilience and adaptability (Rao et al, 2019).…”
Section: Research Implication For Policymakersmentioning
confidence: 99%
“…Two pieces of literature also highlight gender-sensitive approaches that are mostly needed in menstrual hygiene management implementation (Bhattacharjee, 2019;Tufail et al, 2023). The last, gender-perspective approach, which completes the previous three elements due to its emphasis on how women contributed with critical knowledge, capacity and capability, and experiences for ensuring inclusive resilience in disaster risk reduction despite being more vulnerable to disaster and climate change (Chisty et al, 2021;Tobi et al, 2023). Moreover, the gender perspective integrates the importance of acknowledging the different roles, responsibilities, access, and control over resources that men and women have in responding to disasters into all aspects of disaster policy and planning, data collection and analysis of disaster, and decisionmaking processes (Chisty et al, 2021;Sorensen et al, 2018;Yadav et al, 2021).…”
Section: Research Implication For Policymakersmentioning
confidence: 99%
“…Studies report that men farmers, for instance, are found to be more vulnerable to higher temperatures and changes in rainfall patterns [10]. Therefore, neglecting men's and women's differences in adaptation needs can not only exacerbate inequalities but also diminish women's potential as agents of change in the economic sectors that are sensitive to climate change, such as agriculture, energy, and water, as well as disaster risk reduction [5,[11][12][13].…”
Section: Introduction: Gender In the Climate Change Contextmentioning
confidence: 99%